2021
DOI: 10.3892/ol.2021.12651
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT promotes hepatitis B virus replication and liver cancer cell proliferation through the regulation of aerobic glycolysis

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is a critical rate-limiting enzyme involved in NAD synthesis that has been shown to contribute to the progression of liver cancer. However, the potential role and mechanism of NAMPT in hepatitis B virus (HBV)-associated liver cancer remain unclear. The present study assessed the expression of NAMPT in HBV-positive and-negative liver cancer cells, and investigated whether HBV-induced NAMPT expression is dependent on HBV X protein (HBx). In addition, the role of NAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…HBV has been shown to induce metabolic reprogramming to provide energy for HBV replication [ 6 , 7 , 8 ]. HBV infection increases glucose uptake, glycolytic metabolism, and lipid accumulation, which drive hepatic tissue damage resulting in the development of cirrhosis and HCC [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV has been shown to induce metabolic reprogramming to provide energy for HBV replication [ 6 , 7 , 8 ]. HBV infection increases glucose uptake, glycolytic metabolism, and lipid accumulation, which drive hepatic tissue damage resulting in the development of cirrhosis and HCC [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection increases glucose uptake, glycolytic metabolism, and lipid accumulation, which drive hepatic tissue damage resulting in the development of cirrhosis and HCC [ 9 , 10 , 11 ]. Although many metabolic proteins are involved in HBV replication [ 6 , 7 , 8 , 9 , 10 , 11 ], the underlying signaling pathway associated with metabolism during HBV replication has not yet been clearly determined. Evaluation of the metabolic signaling pathways associated with HBV replication showed that the AMPK activator metformin, which is used to treat patients with type 2 diabetes, suppressed the syntheses of HBe and HBs antigens and HBV replicative intermediate (RI) DNAs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, stem cells are more resistant to apoptosis than parenchymal cells in the same tissue, and are able to grow because ATP production has shifted from oxidative phosphorylation to aerobic glycolysis. This metabolic shift appears to be mediated by HBx [ 63 ]. In CLD, the survival and proliferation of cells in cirrhotic nodules, which exist in a hypoxic environment, may result from the “stemness” characteristics conferred onto them by HBx ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C-terminal-activating regions of LMP1 can promote GLUT1 transcription via the mTORC1/NF-κB signaling pathway ( Zhang et al., 2017 ). The hepatitis B virus core protein (HBc) and x protein (HBx) can increase key glycolytic enzymes and related genes NAMPT and NRF2 to enhance glycolysis ( Guo et al., 2021 ; Xie et al., 2017 ). Moreover, HCV severely impairs mitochondrial oxidative phosphorylation to promote HIF-1α expression and transcriptional activation, and its encoded proteins (NS5A and NS5B) can promote glycolytic enzymes’ activity to enhance glycolysis for viral replication ( Ramière et al., 2014 ; Ripoli et al., 2010 ; Wu et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%